2016
DOI: 10.1007/s00417-016-3473-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral cefuroxime in the prevention of postoperative endophthalmitis: an experience from Hong Kong

Abstract: The use of intracameral cefuroxime could significantly reduce the rate of postoperative endophthalmitis in a tertiary centre in Hong Kong. The use of aseptic compounding to prepare cefuroxime aliquots by hospital pharmacy appeared to be safe and efficacious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…[71123] ICC injection during cataract surgery was well tolerated in a prospective study of forty penicillin-allergic patients with a negative preoperative cefuroxime skin test. [24] The use of ICC in patients with penicillin allergy was explored between 2004 and 2012 in a case–control registry study; the control group was the cohort of patients undergoing cataract surgery under a hospital policy of excluding patients with self-reported penicillin allergy.…”
Section: Resultsmentioning
confidence: 99%
“…[71123] ICC injection during cataract surgery was well tolerated in a prospective study of forty penicillin-allergic patients with a negative preoperative cefuroxime skin test. [24] The use of ICC in patients with penicillin allergy was explored between 2004 and 2012 in a case–control registry study; the control group was the cohort of patients undergoing cataract surgery under a hospital policy of excluding patients with self-reported penicillin allergy.…”
Section: Resultsmentioning
confidence: 99%
“…Retrospective studies from Canada, France, South Africa, and Sweden, among other countries, have found significant decreases in the rate of POE with the use of intracameral cefuroxime. In Spain, reductions in endophthalmitis were as high as tenfold with intracameral cefazolin, another cephalosporin [ 40 46 ] A tertiary center in Hong Kong reduced the incidence of endophthalmitis to 0% with the use of intracameral cefuroxime that had been compounded by the hospital pharmacy [ 47 ].…”
Section: Intra-operative Carementioning
confidence: 99%
“…Multiple studies comparing rates of endophthalmitis from time periods before and after IC cefuroxime implementation have shown significantly reduced rates since its introduction. 48,49 A shortcoming of retrospective studies is the failure to account for improvements in surgical and aseptic technique that occurred over the same time periods. 44 Recently, both moxifloxacin and cefuroxime have demonstrated efficacy at reducing endophthalmitis after phacoemulsification compared to controls.…”
Section: Prophylaxismentioning
confidence: 99%